Penanaman Nilai-Nilai Multikultural dalam Pembelajaran Pendidikan Agama Islam untuk Meningkatkan Toleransi di Kelas V SDN Depok 5 Kota Depok - Yumna Nur’aini; Suhendra Suhendra; Andestend Andestend (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
The aim of this research is to find out how multicultural values, learning methods, the impact of multicultural values, and the implementation of instilling multicultural values ​​in Islamic religious education learning to increase tolerance. This research method uses qualitative research with a descriptive approach. This research was carried out at SDN Depok 5, Depok City from May to August 2023, the primary sources were PAI teachers, class V homeroom teachers, principals, and class V students at SDN Depok 5, Depok City, collecting data using observation and in-depth interviews. Data analysis goes through the stages of data collection, data reduction, data presentation, and drawing conclusions. The research results state that multicultural values ​​in PAI learning include human values, togetherness values, and peace values. Instilling multicultural values ​​in Islamic religious learning to increase tolerance at SDN Depok 5 Depok City using lecture and question and answer methods. The impact of instilling multicultural values ​​in Islamic religious learning to increase tolerance at SDN Depok 5 Depok City on students is that they can get used to the diversity that exists both at home and at school. The implementation of instilling multicultural values ​​in Islamic religious learning to increase tolerance at SDN Depok 5 Depok City is to equalize each other and provide additional insight to be able to understand the tagging of independent responsibility between human relationships and their creators.